Workability Analysis of 3D Printing Materials for Applications in The Construction Industry - Ridho Bayuaji; Hendro Nurhadi; Beta Rahayuning Pratiwi; Yuyun Tajunnisa (IPTEK The Journal of Engineering, 2023)
The development of 3D Printing machine technology as a printing tool that uses an additive manufacturing method system with the aim of producing a three-dimensional (3D) object or object according to the default digital design file. 3D Printing was created to facilitate construction work, with 3D Printing construction work becoming lighter because this tool saves time, and costs, and reduces the risk of work accidents. With 3D Printing, work runs quickly and avoids problems in the development process. In the last few decades, many developed countries have used 3D Printing technology in making buildings. The 3D printing process basically consists of three different stages namely, data preparation, material preparation and transfer to the printer, and the printing stage. In the data preparation stage, the components are designed as 3D CAD models, then converted to STL (Stereolithography) format and sliced with the desired layer depth. The preparation of concrete involves mixing and placing it into a container. Once fresh concrete has been placed into the container, it can be channeled smoothly through a pump-pipe-nozzle system to print self-compacting concrete filaments, which build structural components layer by layer. The material used in this 3D printing method was Portland cement where this cement is easy to find among the public. Portland cement itself is the cement that is commonly used as a basic material for making concrete, plaster, mortar, and non-specialized mortar. In addition, fly ash and silica fumes are also added as a mixture. The addition of silica fumes increases the compressive strength of concrete. Furthermore, the addition of fly ash to the concrete has the effect of reducing drying shrinkage; but reducing the compressive strength of the concrete. In this study, the author focuses on the workability of 3D Printing concrete materials, and the impact of the material was added with additional type C fly ash and silica fume, namely flowability. The result is a concrete mix design that has good flowability value to be applied to the 3D Printing method.